Cover Picture: Mononuclear and Terminal Zirconium and Hafnium Methylidenes (Angew. Chem. Int. Ed. 41/2014). Issue 41 (27th August 2014) - Kamitani, Masahiro; Pinter, Balazs; Chen, Chun‐Hsing; Pink, Maren; Mindiola, Daniel J.
<x xml:space="preserve">Abstract</x> Kinetically stable methylidene complexes of zirconium and hafnium were prepared through photolysis‐induced α‐H abstraction from the corresponding complexes with aryloxide and two methyl ligands. In their Communication on page 10913 ff., D. J. Mindiola and co‐workers describe their quest for a kinetically more resistant system (structure on top of the compass) by taking advantage of prior systems (old map with drawings), thus finding the target molecule (inside the treasure chest).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>